Hierarquias integráveis supersimétricas - Lobo, Gabriel Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Estudamos hierarquias integráveis. Essas hierarquias possuem infinitas equações de movimento que emergem de uma mesma estrutura algébrica. Algumas equações são conhecidas como mKdV e Sinh-Gordon, estas equações possuem extensão supersimétrica. Isso nos conduz a construção de hierarquias supersimétricas e possamos assim obter infinitas equações com supersimetria. Para construir essas hierarquias não fazemos uso de formalismo como supercampos, as relações de supersimetria surgem da própria construção algébrica. Além disso investigamos para dada uma superalgébra como construir sistematicamente hierarquias supersimétricas e ainda explicitamos diversas propostas de hierarquias e discutimos os principais resultados obtidos.

We study integrable hierarchies. These hierarchies have infinite equations of motion that emerge from the same algebraic structure. Some equations are known as mKdV and Sinh-Gordon, these equations have supersymmetric extension. This leads us to the construction of supersymmetric hierarchies and we can thus obtain infinite equations with supersymmetry. To construct these hierarchies we do not use formalism as superfields techniques, the relations of supersymmetry emerge from the algebraic construction itself. In addition we investigate for given a super algebra how to systematically construct supersymmetric hierarchies and we also explain several proposals of hierarchies and we discuss the main results obtained.

modelos integráveis
Supersymmetric integrable hierarchies
Keywords: Hierarquias integráveis; Supersimetria; Modelos integráveis; Integrable hierarchies; Supersymmetry; Integrable models